Pelatihan Cara Hemat, Nyaman, dan Praktis Pembuatan Hand Sanitizer Berbahan Herbal - Al Khudri Sembiring; Rikizaputra; Marta Dinata (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Alcohol is widely used as an antiseptic / disinfectant for clean skin surface disinfection, but not for injured skin. In addition, alcohol also has properties that are irritating to the skin, it burns easily, and also increases viral infections that trigger inflammation of the digestive tract, so the idea emerged to use natural ingredients that can reduce the risk of developing digestive disorders. The methods used to achieve the goal are pretest, lecture, direct practice, extension media, and posttest. Based on the results and discussion, it can be concluded that this service activity gives positive results. This is because this activity can help with difficulties and meet the participants' needs in maintaining health protocols by skillfully making natural hand sanitizers from Piper sp. leaves. After this service activity is complete, participants should stay active and be even more active in understanding the use of herbal hand sanitizers.